Analisis Pembangunan Infrastruktur pada Kawasan Perumahan dengan Pendekatan Arsitektur Berkelanjutan : (Studi Kasus Perumahan Boulevard Kecamatan Kambu Kota Kendari) - Taufiq, Elvina Sari; Abidin, Afri Ahyarky; Sirhadi, Jabar (Universitas Muhammadiyah Kendari, 2026)
Housing is a group of houses that function as a residential or residential environment. In general, housing and settlements often have many problems. The purpose of this study is to determine the condition of facilities and infrastructure and environmental utilities in the Boulevard housing complex, Kambu District, Mokoau Village, Kendari City. This study uses the Field Research method, by conducting observations and documentation as well as conducting interviews in order to find detailed and detailed data in the field by observing from the smallest phenomena that become a reference for problem points, to observing the largest phenomena and trying to find solutions to these problems. The results of this study reveal facts related to problems with facilities and infrastructure and environmental utilities in the Boulevard Housing Complex, Kambu District, Mokoau Village, Kendari City, which are then analyzed and designed to create a comfortable, orderly and independent environment in accordance with the concept of sustainable architecture.